2022
DOI: 10.1039/d1cc06769a
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasound activated cyanine-rhenium(i) complex for sonodynamic and gas synergistic therapy

Abstract: A novel cyanine-rhenium(I) tricarbonyl complex is developed as a potent sonosensitizer and sono-activatable CO-releasing agent for sonodynamic therapy (SDT) and CO gas therapy by inducing ferroptosis in cancer cells. This...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…Several recent studies have demonstrated the versatile therapeutic potential of nanomaterials that reveal induced-shear force as a sonodynamic effect causing LPO and ferroptosis. 41–44…”
Section: Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have demonstrated the versatile therapeutic potential of nanomaterials that reveal induced-shear force as a sonodynamic effect causing LPO and ferroptosis. 41–44…”
Section: Ultrasoundmentioning
confidence: 99%
“…Several recent studies have demonstrated the versatile therapeutic potential of nanomaterials that reveal induced-shear force as a sonodynamic effect causing LPO and ferroptosis. [41][42][43][44] In 2021, Chen et al demonstrated synergistic tumor treatment via an SDT-based LPO mechanism to induce ferroptosis using ferumoxytol and a PpIX sonosensitizer (Fig. 4b).…”
Section: Sono-shear Force-mediated Cancer Therapymentioning
confidence: 99%
“…To date, several gases, such as nitrogen (N 2 ), and nitric oxide (NO), carbon oxide (CO), carbon dioxide (CO 2 ), have been involved in these therapeutic approaches ( Chen et al, 2019 ). When SDT is combined with gas therapy for tumor treatment, the US triggers gas donors to release and produce highly toxic products or change the disease condition to promote the tumor suppression effects ( An et al, 2020b ; Cheng et al, 2022 ; Zhu et al, 2022 ; Zuo et al, 2022 ). The generated gas bubbles could be used as a powerful US contrast agent that greatly enhances the US contrast to guide cancer therapy.…”
Section: Sonodynamic Therapymentioning
confidence: 99%
“…[43] To overcome this drawback, Zhang and co-workers have tried to realize the potential of Re(I)-based CO-releasing molecules (1-4) (Figure 2) in SDT. [44,45] Complex 2 displayed higher CO release than 1 because of the Cy (cyanine) ligand pendant. Cyanine moieties with more conjugation increase the π-π conjugate plane, which enhances the sonosensitivity of 2.…”
mentioning
confidence: 99%
“…These complexes released most of the Re(I)-attached CO after US irradiation, evident from gas chromatography and fluorescence studies using CO probe COP-1. [44,45] Hemoglobin (Hb) assay [46] was used to quantify the amount of CO released after US irradiation. It shows that 1.0 mole of Re complexes released ca.…”
mentioning
confidence: 99%